The Effect of Pineapple Juice on The Healing of Postoperative Sectio Caesarea Wounds at Bogor City Mulia Pajajaran Hospital in 2023 - Melani, Nurrima; Silawati, Vivi; Azzahroh, Putri (Rajaki of Tulip Medika Publisher, 2023)
Background: According to RISKESDAS in 2018, the number of childbirths using the sectio caesarea method in women aged 10-54 years in Indonesia reached 17.6% of the total number of deliveries. Recovery in the puerperium for mothers who have given birth by sectio caesarea surgery can be done by gradual early mobilization, because there is an incision wound on the abdomen of the mother. In addition to the mobilization of factors affecting wound healing is the intake of maternal nutrients. The role of nutrition in wound healing is very important in wound healing. Nutrient intake is high in protein such as in fish, eggs and fruits. Pineapple fruit can accelerate wound healing because there is a bromelain enzyme that can convert protein into amino acids that can regenerate damaged cells so that wound healing will take place faster. Purpose: To know the Effect of Pineapple Juice on The Healing of Postoperative Sectio Caesarea Wounds at Bogor City Mulia Pajajaran Hospital in 2023 Methods: This research is a quasi-experiment with a pre-posttest only control group research design. The sampling technique uses non probability sampling with accidental sampling method. The samples in this study were calculated by large samples with a paired numerical analytical formula with the results of a large sample of 32 samples, and the group was divided into 2, namely the control group and the intervention group. Data collection is carried out by observation. Data analysis was performed using the Wilxocon Test. Results: Based on the results of the study showed that there was an effect of giving Pineapple Juice on wound healing in postoperative sectio caesarea mothers with a p-value of 0.000 meaning < 0.05. Conclusion: Consumption of Pineapple Juice can speed up the healing process of postoperative sectio caesarea wounds at Mulia Pajajaran Hospital, Bogor City. It is hoped that consuming pineapple juice can be recommended and applied by health workers to postpartum mothers whose delivery is by sectio caesarea surgery.